Electroacupuncture Alleviates Surgical Trauma-Induced Hypothalamus Pituitary Adrenal Axis Hyperactivity Via microRNA-142 - Zhu, Jing; Chen, Zhejun; Meng, Zehui; Ju, Minda; Zhang, Mizhen; Wu, Gencheng; Guo, Haidong; Tian, Zhanzhuang (Frontiers in Molecular Neuroscience, 2017)
Electroacupuncture (EA) could improve the hyperactivity of the hypothalamus pituitary adrenal (HPA) axis induced by hepatectomy. However, its underlying mechanism still remains largely unclear. Here, we found that hypothalamic corticotrophin releasing hormone (CRH) modulates the function of the HPA axis, while hepatectomy induced an HPA axis disorder and EA application could regulate the hypothalamic CRH. We first demonstrated that microRNAs (miRNAs) target on CRH via bioinformatics analysis and screened them in the primary hypothalamic neurons. MicroR-142 (miR-142) and miR-376c were identified to inhibit CRH at the mRNA and protein levels, and a dual luciferase reporter assay confirmed their binding to the 3′-untranslated regions (3′-UTR) of CRH. Further analyses revealed a decrease in hypothalamic miR-142 expression in the hepatectomy rats and an increase in miR-142 and miR-376c after EA intervention. Importantly, the improvement effect of EA on the HPA axis regulatory function in hepatectomy rats was blocked by miR-142 antagomir. Our findings illustrated that EA could up-regulate hypothalamic miR-142 expression and decrease the CRH level to alleviate the hyperactivity of the HPA axis induced by hepatectomy.